e-AGROBOT- A Robot for Early Crop Disease Detection using Raspberry Pi - G. Kalyani, K. Amrutha, S. Alekhya, S. Lalitha Samrajyam, D. Chaya Sirisha, Y. Yamini, V. Meghana (International Journal of Advanced Science and Technology, 2020)
India is a farmland with population of three-fourth in the agriculture. As we know agriculture sector is rapidly diminishing day by day which mainly affects the enhancement of the Human Life. This project mainly deals with exploring of how robotics can be applied to various agriculture fields. The main strategy of this project is to improve efficiency and productive rate of agriculture crops. This can be done by replacing the human laborer’s by active machines like robots by using latest technologies. In this project, we mainly introduce e-Agrobot a robot which mainly identifies the crop disease through image processing techniques using Raspberry Pi. It also performs operations like detection of presence of pests, spraying of pesticide,thereby providing safety to the farmers. The developed system involves a prototype which uses simple cost-effective electronic devices like Ultrasonic sensor, Raspberry-Pi and various motors which is an aid to the farmers about the plant health through IOT.Keywords: Raspberry-Pi, Robot, Sensors, Crop disease detection, Image Processing, Pesticide spraying, IOT.